Prefilter bandwidth effects in data symbol phase synchronizers of open loop - Reis, A.D. (2010)
This work studies the effects of the prefilter bandwidth on the open loop symbol synchronizers. We consider three different prefilter bandwidth, namely, B1=¥ ( infinite), B2=2.tx and B3=1.tx, where tx is the transmission rate. We consider also four open loop symbol synchronizers, namely, the tank (tank), the SAW (SAW), the monostable (mon), and the astable (ast). The objective is to study the prefilter bandwidth with the four open loop symbol synchronizers and to evaluate their output jitter UIRMS (Unit Interval Root Mean Square) versus input SNR (Signal to Noise Ratio).